2021
DOI: 10.1155/2021/2168595
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Safety, Efficiency, and Signal Pathways of Stem Cell Therapy for Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease that affects multiple organs and tissues. Mesenchymal stem cells (MSCs) are considered a good source for autoimmune disease and hematological disease therapy. This review will summarize the efficacy, safety, and mechanisms of MSC therapy for SLE. MSC therapy can reduce anti-dsDNA, antinuclear antigen (ANA), proteinuria, and serum creatinine in SLE patients. In animal models of SLE, MSC therapy also indicates that it could reduce anti-dsDNA, ANA, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…All studies appraised in this systematic review successfully demonstrated significant improvement in SLEDAI scores. Besides reducing proinflammatory cytokines, such as IL‐23, IL‐17, monocyte chemoattractant protein‐1, and high‐mobility group box chromosomal protein 1, MSCs can also promote upregulation of anti‐inflammatory cytokines, including IL‐4, prostaglandin E2, transforming growth factor beta, and IL‐10 23 . The resulting anti‐inflammatory effect leads to delayed organ damage and reduced disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…All studies appraised in this systematic review successfully demonstrated significant improvement in SLEDAI scores. Besides reducing proinflammatory cytokines, such as IL‐23, IL‐17, monocyte chemoattractant protein‐1, and high‐mobility group box chromosomal protein 1, MSCs can also promote upregulation of anti‐inflammatory cytokines, including IL‐4, prostaglandin E2, transforming growth factor beta, and IL‐10 23 . The resulting anti‐inflammatory effect leads to delayed organ damage and reduced disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial‐based study, transplantation of allogeneic UC‐MSCs in patients with type 2 diabetes resulted in significant improvements in diabetes status, reductions in insulin requirements and insulin independence during follow‐up, and no immediate or long‐term side effects associated with cell infusion during treatment 106 . MSCs treatment also reduced anti‐dsDNA, antinuclear antigens, proteinuria, and serum creatinine in systemic lupus erythematosus (SLE) patients without serious adverse events, treatment‐related mortality, or tumour‐related events 107,108 . There are also many reports of successful application in other system intractable diseases 109–111 …”
Section: Perspectivementioning
confidence: 99%
“…106 MSCs treatment also reduced anti-dsDNA, antinuclear antigens, proteinuria, and serum creatinine in systemic lupus erythematosus (SLE) patients without serious adverse events, treatment-related mortality, or tumour-related events. 107,108 There are also many reports of successful application in other system intractable diseases. [109][110][111] In conclusion, allogeneic MSCs therapy has a good prospect for the treatment of a variety of difficult clinical diseases.…”
Section: Perspectivementioning
confidence: 99%
“…However, heterogeneous presentation of lupus in humans presents a challenge, and mouse models may not represent a complete spectrum of pathogenesis but only a subset of changes observed in the human population [ 84 ]. A comprehensive review of the safety, efficacy, and signal pathways of stem cell therapy of SLE [ 68 ] suggested an immense potential for clinical applications. Allogenic MSC transplantation with peripheral blood MSCs in three lupus nephritis patients resulted in decreased serum creatinine levels.…”
Section: Preclinical Animal Models Of Autoimmune Diseasesmentioning
confidence: 99%
“…MSCs have the potential to regulate the immune system and control inflammation by inhibiting the activation of NF-κB and JACK/STAT and Akt/GSK3β signalling pathways to ameliorate SLE lesions [67]. Hence, MSCs have been extensively explored for the treatment of SLE in experimental animals [29,68] and human patients [2,8]. MSCs exert immunosuppressive effects through proinflammatory cytokine secretion and inhibiting lymphocyte activation and 3 Stem Cells International proliferation.…”
Section: Systemic Lupusmentioning
confidence: 99%